Advancement of Loans and It’s Repayment behavior- A Study of Self Help Groups in region of Punjab - Sharma, Dr. Rasna; Chopra, Ms. Sheena (The journal of contemporary issues in business and government, 2021)
For Women Empowerment and economically weaker group of people who come together to pool some amount of money from small savings on regular basis which is then deposited in a common pool to meet the immediate and emergency needs of the Self Help Group members by providing them loans free from collateral to fulfill the purpose. Self Help Groups is a homogeneous group who has joined their hands and supports each other to overcome the problems they usually face. The loan amount is decided by the SHG members and also the time period of its repayment. The member who defaults will not be getting another loan till he repays the older one. This study focuses on such groups who are pooling their money, taking loans and repays them within stipulated time period. The study has been done in the highly populated districts of Punjab with the sample size of 500 members. Various statistical tools have been applied such as percentage method and Chi Square to check any the relationships in their attributes.